Incidence and Survival for Gastric and Esophageal Cancer Diagnosed in British Columbia, 1990 to 1999 - Morteza Bashash; Amil Shah; Greg Hislop; Angela Brooks-Wilson; Nhu Le; Chris Bajdik (Canadian Journal of Gastroenterology)
BACKGROUND: Geographical variation and temporal trends in the incidence of esophageal and gastric cancers vary according to both tumour morphology and organ subsite. Both diseases are among the deadliest forms of cancer. The incidence and survival rates for gastric and esophageal carcinoma in British Columbia (BC) between 1990 and 1999 are described.